Purtscher-Like Retinopathy in a Patient with COVID-19 - Alexander R. Bottini; Sean Steinmetz; Kevin J. Blinder; Gaurav K. Shah (Case Reports in Ophthalmological Medicine)
The emerging literature on the novel coronavirus pandemic has reported several cases of varied retinal findings in patients with COVID-19. We report the case of a 59-year-old male who presented with complaint of bilateral blurry vision following hospital discharge after prolonged hospitalization for severe COVID-19 illness. On ocular exam, the patient demonstrated bilateral cotton wool spots localized to the posterior pole of each eye. Multimodal imaging demonstrated findings consistent with retinal nerve fiber layer infarcts in the areas of the cotton wool spots. Exam and imaging of our patient were most consistent with a Purtscher-like retinopathy. We suggest that as ophthalmologists care for increasing numbers of patients recuperating from COVID-19, they monitor for microangiopathic changes similar to those in our patient.